Implementasi Metode SAW dalam Sistem Pendukung Keputusan Pemilihan Laptop Menggunakan Scratch - Fahrik Huzaeni; Indra Igun Gunawan (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2022)
Increasingly sophisticated technology makes humans have to participate in technological advances. Like laptops, the development of technology, the technology used by laptops is getting better, such as better specifications and making buyers more difficult because there are many laptops available today. With this research entitled the implementation of the SAW method in the laptop selection decision system, it is hoped that prospective buyers can see and compare the weighting methods starting from the brand criteria and features that can make it easier for prospective laptop buyers to determine their choices that can adjust to the needs that will be used. In this research there are 2 laptops (alternatively include Acer and Asus). The result is Asus which is laptop 2 to rank 1 with a value of 0.6, Acer rank 2 with a value of 0.45.